식생활라이프스타일에 따른 중장년층과 노년층의 HMR 제품 구매행동과 선택속성에 대한 연구: 서울, 경기지역을 중심으로 - 정유빈(Yu-Bin Jeong); 황희원(Hee-Won Hwang); 정효재(Hyo-Jae Jung); 오지은(Ji-Eun Oh) (한국콘텐츠학회 논문지, 22(2), 2022)
Korea's aging population is rapidly increasing, but there has been little research into senior-friendly foods. Therefore, this study aimed to provide basic data for the development of senior-friendly Home Meal Replacement(HMR) foods by conducting a survey among elderly and middle-aged persons highly likely to purchase senior-friendly foods in the near future. Study findings showed that the level of HMR purchase was higher among the middle-aged, many subjects preferred products requiring simple cooking, and a higher proportion of subjects purchased them offline. Five HMR selection attributes were identified, and dietary lifestyles were classified into four categories. Through a cluster analysis, 3 groups based on level of involvement were identified: high-level, mid-level, and low-level. Napping® analysis showed that subjects classified food products into HMR and meal kits, and into products with a clear broth and products with a thicker broth. The study findings are expected to help suggest a differentiating approach in developing senior-friendly HMR foods. 우리나라의 고령인구는 빠른 속도로 증가하고 있으나, 고령친화식품에 관한 연구는 부족한 실정이다. 따라서 본 연구는 현 고령자와 향후 고령친화식품 구매 가능성이 큰 중장년층을 대상으로 설문을 진행 및 분석하여 고령 친화 Home Meal Replacement(HMR) 식품개발의 기초자료를 제시하고자 하였다. 연구 결과 HMR 구매 경험은 중장년층이 높았으며, 간단 조리 후 먹는 음식을 선호하는 응답자가 많았고, 오프라인을 통한 구매 비율이 더 높게 나타났다. HMR 선택속성 요인은 5개로, 식생활 라이프스타일은 4개로 나뉘었으며, 군집분석 결과 고관여, 중관여, 저관여 집단으로 분류되었다. Napping® 분석 결과, 제품을 HMR과 밀키트, 국물이 맑은 제품과 진한 제품으로 구분하고 있음을 확인하였다. 본 연구결과는 고령친화 HMR 식품개발 시 차별적인 방안을 제시하는 데 도움이 될 것이라 기대한다.